POLA PERESEPAN ANTIBIOTIK PADA PASIEN ANAK DENGAN INFEKSI PERNAPASAN AKUT - Munandar, Dzukharian; Bangnga, Nina Safiah; Tukayo, Brechkerts Lieske Angruni; Soegiharti, Pratiwi (Poltekkes Kemenkes Bandung, 2023)
Prescriptions for children who experience upper and lower acute respiratory infections (ARI), such as the common cold, rhinitis, sinusitis, pharyngitis and tonsillitis, are carried out according to the pattern. The study aimed to determine the pattern of antibiotic prescribing in pediatric ARI patients at the Karadiri Community Health Center, Nabire Regency. This type of descriptive research uses secondary data, namely medical records of antibiotic prescriptions in pediatric patients with ARI. The sample was all medical records of pediatric patients treated with ARI at the Karadiri Community Health Center, Nabire Regency, totaling 92 respondents. Sample selection with inclusion criteria is complete data, residents who live in the work area of the health center, and exclusion is incomplete data and non-residents who are disabled in the work area of the health center. The instrument uses an observation sheet. The results showed that the majority of ARI patients were aged 2-5 years (85%) and male (54%). The antibiotics used were amoxicillin in 58 patients (63%), followed by Co-trimoxazole in 25 (27%), Erythromycin in 9 (10%). The most commonly prescribed antibiotic dose was amoxicillin 66.7 mg (32%) with 24 prescriptions (26%). The duration of antibiotic administration was 5 days for 89 prescriptions (97%), with 67 prescriptions (75%) meeting the guidelines. In conclusion, the prescription of antibiotics for pediatric patients with ARI is not fully in accordance with the guidelines, namely the duration is 4 days and the dose follows the patient's body weight.